2019
DOI: 10.1016/j.jcot.2018.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric elbow measurement parameters: Evaluation of the six angles in inter- and intra-observer reliability

Abstract: Background: Several radiographic measurements of the humerus can be used to evaluate the treatment outcome of supracondylar fractures in children. Because of the cartilaginous nature of the immature elbow, interpretation of radiographs around this area is sometimes challenging and can be unreliable. This study was conducted to determine the inter-observer and intra-observer reliability of the six commonly used radiographic measurements of the distal humerus. Method: The Baumann angle, humero-ulna angle, metaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
(12 reference statements)
3
10
0
Order By: Relevance
“…showed that all the AHL in the age range 0–5 years intersected with the middle one‐third of the capitellum, but in 30% of children under the age of 2 years, it intersected with the anterior one‐third of the capitellum. The previous reports provide evidence of the significance of the capitellum as one of the landmarks affecting reliability in elbow measurement.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…showed that all the AHL in the age range 0–5 years intersected with the middle one‐third of the capitellum, but in 30% of children under the age of 2 years, it intersected with the anterior one‐third of the capitellum. The previous reports provide evidence of the significance of the capitellum as one of the landmarks affecting reliability in elbow measurement.…”
Section: Introductionmentioning
confidence: 84%
“…A report of a late presented pediatric supracondylar fracture by Mulpruek et al . found that SCA can be the intraoperative reference for correction of sagittal alignment of the pediatric elbow. In terms of reliability, Suangyanon et al .…”
Section: Introductionmentioning
confidence: 99%
“…The lateral capitellohumeral angle (LCHA) is the angle between humeral shaft and the capitellum on lateral x-rays of the elbow and is a measure of the sagittal plane alignment [8]. The normal values of these angles were noted in several previous publications [9][10][11][12]. We used the values provided by Shank et al as reference values for comparison with the BA and LCHA on final clinical x-rays on our patient population as this was a good study that provided mean BA and LCHA in normal uninjured children along with standard deviation [9].…”
Section: Definitionsmentioning
confidence: 99%
“…16 It has been reported that the anterior margin of the humeral cortex normally goes through the middle third of the capitellum in the lateral view of the elbow; 17 therefore, the relationship between the anterior margin of the humerus (AMH) and the capitellum may be used to depict the degree of elbow deformity. 18 To date, there have been no reports quantifying the possible loss of elbow motion based on the relationship between the AMH and capitellum using the lateral view. In this study, we simulated Gartland IIA SCFs in the lateral view of normal pediatric elbows.…”
Section: Introductionmentioning
confidence: 99%
“…However, this angle does not reflect clinical function loss 16 . It has been reported that the anterior margin of the humeral cortex normally goes through the middle third of the capitellum in the lateral view of the elbow; 17 therefore, the relationship between the anterior margin of the humerus (AMH) and the capitellum may be used to depict the degree of elbow deformity 18 …”
Section: Introductionmentioning
confidence: 99%